Open Government Data Maturity Assessment at the General Elections Commission of Indonesia Using the OD-MM Model - Sa’adah, Salma; Pramono, Sidik (Jayapangus Press, 2025)
The General Elections Commission of the Republic of Indonesia (KPU RI) plays a crucial role in ensuring electoral transparency through data openness. In response to growing demands for openness, KPU RI launched the Open Data KPU platform. However, in the context of the 2024 General Elections, challenges such as data leakage, fragmented portals, system inaccuracies, and the absence of unified regulations under the One Data Indonesia initiative continue to hinder the effectiveness of open government data (OGD) implementation. These issues not only obstruct data governance but also risk undermining public trust in electoral integrity. To address this, the study assesses KPU RI’s OGD maturity using the Open Data Maturity Model (OD-MM) by Solar et al., through a qualitative approach combining expert interviews and document analysis. The findings reveal that KPU RI’s OGD maturity level remains at Level 2, categorized as Emerging Capacities, which indicates that capabilities to meet the required criteria have begun to appear, with similar procedures being carried out, but without formal standards or documented processes. By applying the OD-MM framework in an electoral data context, this research offers insights for improving OGD governance in public institutions and enhancing the effectiveness of digital democracy initiatives.